Predictable Scheduling for a Soft Modem - Jones, Mike; Saroiu, Stefan (2000)
Soft Modems use the main processor to execute modem functions traditionally performed by hardware on the modem card. To function correctly, soft modems require that ongoing signal processing computations be performed on the host CPU in a timely manner. Thus, signal processing is a commonly occurring background real-time application — one running on systems that were not designed to support predictable real-time execution. This paper presents a detailed study of the performance characteristics and resource requirements of a popular soft modem. Understanding these requirements should inform the efforts of those designing and building operating systems needing to support soft modems. Furthermore, we believe that the conclusions of this study also apply to other existing and upcoming soft devices, such as soft Digital Subscriber Line (DSL) cards. We conclude that (1) signal processing in an interrupt handler is not only unnecessary but also detrimental to the predictability of other computations in the system and (2) a real-time scheduler can provide predictability for the soft modem while minimizing its impact on other computations in the system.